Fostering Improvement: a reflection on equity-centered improvement across three initiatives - Eubanks, Segun; Neumerski, Christine M.; Callahan, Pamela Catherine; Anthony, Douglas; Snell, Jean; Blondonville, Damaries; Viviani, William; Liccione, Laura (Frontiers in Education, 2024)
In this conceptual piece, we explore the emerging definition of equity-centered improvement in education. We describe how the Center for Educational Improvement and Innovation, a partnership center at the University of Maryland College Park, both conceptualizes and operationalizes equity across three initiatives: (1) a district-embedded networked improvement community focused on math achievement and social/emotional learning; (2) a school improvement leadership academy which offers evidence-based professional learning to principals and assistant principals serving in high need schools in Maryland and New Jersey; and (3) a racial and social justice collaborative utilizing a research-practice partnership to address issues of equity within Maryland school districts. We present this article as a type of “reflective practice” as we consider how equity-focused continuous improvement plays out across these three initiatives. In focusing on how each initiative embeds and develops equity-focused improvement practices, we investigate the connection between our shared understanding of equity and its implementation.